An Analysis of Environmental, Social, and Corporate Governance (ESG) Ratings of Lean Versus Non-Lean Companies - Bunker, Randall B.; Harris, Dan; Cagle, Corey S. (Journal of Accounting and Finance, 2022)
Lean manufacturing is a business philosophy concerned with continually eliminating waste from business processes while producing quality products with greater efficiency. In addition to profits, organizations worldwide are beginning to focus on environmental, social, and corporate-governance (ESG) factors because of the changing global environment. The Environmental Protection Agency has specifically stated that many organizations have found that implementing lean manufacturing concepts and tools results in improvements in environmental performance. This study uses a matched-pairs design, matching lean companies with non-lean companies, and assesses whether lean companies experienced better Sustainalytics ESG risk ratings than non-lean companies. Results show that lean companies achieved more favorable ratings in environmental, social, and corporate-governance factors than did non-lean companies.